Transformation of Number System Learning through an Interactive Number Stacking Game for Elementary School Students - Rachmalia Vinda Kusuma; Saeful Mizan (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
This study aims to examine the effectiveness of an Interactive Number Stacking Game in improving elementary school students’ understanding of the number system, particularly place value concepts. The research employed a quantitative descriptive approach using a one-group pretest–posttest design. The subjects consisted of 34 fourth-grade students at SDN Jadi 2 in the 2024/2025 academic year. Data were collected through pretest and posttest instruments, student response questionnaires, and classroom observations. The pretest and posttest scores were analyzed descriptively to identify learning improvement, while questionnaire data were analyzed using percentage-based descriptive statistics. The results showed that the average pretest score was 81.47, which increased to 85.88 in the posttest, indicating a learning improvement of 5.42%. Based on the assessment criteria, student performance improved from the “Good” category to the “Very Good” category. In addition, questionnaire results revealed that students responded positively to the use of the Interactive Number Stacking Game, demonstrating high levels of interest and engagement during the learning process. Observational data further supported these findings, showing increased student participation and active involvement. These findings indicate that the Interactive Number Stacking Game is effective as an alternative learning media to support students’ conceptual understanding of place value in elementary mathematics learning.